2014
DOI: 10.1590/0103-5150.027.001.ao11
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a health promotion and fall prevention program in elderly individuals participating in interaction groups

Abstract: Introduction Falls in elderly people are an increasing public health problem resulting in high costs to health services. Thus, it is essential to invest in the development of actions and programs focused on decreasing such risks. Objective To verify the effects of a program of health promotion and prevention of falls in relation to balance and functional abilities in elderly people participating in interaction groups in Caxias do Sul City, RS State. Materials and methods For this purpose, 14 elderly people wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 17 publications
3
9
0
7
Order By: Relevance
“…They also show an improvement in the physical performance, activity and agility of the elderly assessed. Current results agree with a study by Pagliosa and Renosto (2014) who, with TUG within the pre-intervention phase, pinpointed a mean rate of 14 s for the execution of the test. After a two-month intervention, a statistically significant decrease in duration was achieved, namely, an improvement in performance, fastness and equilibrium while gait training.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…They also show an improvement in the physical performance, activity and agility of the elderly assessed. Current results agree with a study by Pagliosa and Renosto (2014) who, with TUG within the pre-intervention phase, pinpointed a mean rate of 14 s for the execution of the test. After a two-month intervention, a statistically significant decrease in duration was achieved, namely, an improvement in performance, fastness and equilibrium while gait training.…”
Section: Resultssupporting
confidence: 90%
“…Ten s is the period classified for the elderly without changes in equilibrium and with low fall risks, considered normal for healthy and independent adults; 11 and 20 s is the period for elderly people without any important equilibrium changes, partially independent but with some weaknesses and average fall risks; a period higher than 20 s is a significant deficit in physical mobility and fall risks (Podsiadlo & Richardson, 1991;Gonçalves, Ricci, & Coimbra, 2009;Pagliosa & Renosto, 2014). Most elderly people in current study revealed duration higher than or equal to 12 s for the TUG test, indicative of average risk in falls.…”
Section: Resultsmentioning
confidence: 99%
“…Being female, aged 60 to 69 years and living with a significant other were the majority among the elderly who suffered a fall. Studies have shown that being female is a risk factor for falls (5,10,25) . The prevalence of elderly women in the context of aging is due to the higher life expectancy, being called feminization of old age.…”
Section: Discussionmentioning
confidence: 99%
“…The fall, an unintended event that results in the change of the initial position of the individual to the same level or to a lower level (2) , has its prevalence altered according to the characteristics of the studied elderly population-ranging from 10.7 to 32.1% for the elderly living in the community, since, in institutionalized older adults, that is, residents of long-term institutions, this number increases (66.7%) (3)(4)(5)(6)(7)(8) . These data reveal the vulnerability to which elderly people are exposed (7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…This difference can be explained by the physical activity level of the groups, as 43.3% of the NPTG was considered active by the IPAQ against 13.3% of the PTG. Pagliosa and Renosto 27 proposed a physical activity protocol for a group of elders for two months. At the end of the treatment, they noticed an improvement on balance and gait performance, thus reducing risk of falls.…”
Section: Discussionmentioning
confidence: 99%